A multianalysis thermography‐based approach for fatigue and damage investigations of ASTM A182 F6NM steel at two stress ratios. Issue 1 (12th August 2018) - De Finis, Rosa; Palumbo, Davide; Galietti, Umberto
Abstract: Infrared thermography allows an alternative energy‐based approach for studying the fatigue behaviour of materials to better understand damage phenomena. In particular, the methodology of infrared thermography can explain the complex dissipative mechanisms promoted by the input parameters, such as the loading ratio, can rapidly provide information about the fatigue strength, and has low cost. In this work, analysis of the thermographic sequences of ASTM A 182 grade F6NM steel obtained during fatigue testing provided four thermal indexes that were used to investigate the thermoelastic and plastic behaviour of material. Fatigue tests at two opportunely chosen loading ratios ( R = −0.1, R = 0.5) were performed to investigate the relation between the material behaviour and each index at a specific loading ratio. Finally, estimation of the fatigue strength by means of suitable analysis procedures allowed for an investigation of the damage behaviour of materials under specific loading conditions.